SCHOOL POLICIES IN MAINTAINING SCHOOL CULTURE FOR STUDENTS DURING COVID 19 AT PRIVATE SCHOOL IN DURI - MONA EKAWATI; PUTRI ASILESTARI; RUSDINAL RUSDINAL; SUFYARMA MARSIDIN (CV KULTURA DIGITAL MEDIA, 2020)
This research aims to explore the distribution and the implementation of school policies in maintaining school culture for students during the COVID-19 pandemic in private schools in Duri. During the Pandemic Covid 19, it was a terrible situation in teaching and learning implementation process for students, especially in terms of maintaining an effective school culture such as the 5S culture, worship on time, learning discipline, and carrying out 10 student competencies according to JSIT standards, and also providing excellent services to students. The research method was qualitative with interviewing the principal, student representatives, and the student's parents represented by the school committee and document analysis was used in this research. The research data were analyzed with descriptively by describing and explaining the data from the interview findings of the principal, student representatives, teachers and parents of students, policy documents as well as photos and learning media. The finding revealed that the school policiesimplemented in maintaining school culture for students were not optimal even though all students responded to programs that had been compiled and socialized by the school.Teachers of a foundation implemented character-based learning to maintain School Culture that reflects the existence of an applied school culture such as the 5 S, study of the Koran delivered by the teacher at the beginning of learning, and monitoring sheets provided by student representatives who will be responded to by the students' parents then reported to the homeroom teacher every month. In the process of socializing the policy from the principal, it has been going well where the school has conducted outreach to vice principals, teachers and provided a school culture training system to students online and to teachers and explains learning information to parents. However, due to network limitations and network disruption, it becomes an obstacle in the implementation of monitoring school culture. In this case the teacher composed a monitoring questionnaire manual report material and distributes it to the parents of students. Although the student did not get involveda 100% due to several factors such as network disruption, for those parents who works and parents who do not have facilities in the form of an internet package or do not have an Android cellphone, the process of monitoring school culture continues with the help of manual media provided to parents students. It can be concluded that the dissemination of learning policies during the outbreak has been running from the top-down (Top-Down) socialization process, but implementation needs to be improved in terms of service and the school culture evaluation process can be maintained.